ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENINGKATAN JUMLAH SISWA PADA LEMBAGA PENDIDIKAN NON FORMAL BRITON INTERNATIONAL ENGLISH SCHOOL DI MAKASSAR - Andi Widiawati; Ririn Oktavia Sari (AkMen JURNAL ILMIAH, 2017)
This research was purposed to determine the factors of academic motivations, career development and corporate brand image which affect the increase of student numbers at non formal English course Briton International English School among the courses business competition. The models used in this research were the method of documentation, questionnaire, and literature study using Likert scale. The method to determine the sample was purpose sampling and the analysis method was multiple linear regression method. The results of this research showed the variables of academic motivations, and brand image had significant and positive influences in increase of student numbers at non formal English course Briton International English School, while career development had positive influences but not significant parcially in increase of student numbers at non formal English course Briton International English School. The results of this research also showed the variabel of brand image is the dominan variabel influences in increase of student number at non formal English course Briton International English School. The implications of this research was purposed to help the corporate to be able to maintain the brand image as the main marketing strategy, for example by maintaining quality and providing the service to fulfill the variety of customer needs in learning English as the challenges to face ASEAN Economic Community (AEC) today.